Barriers to electronic procurement adoption in the construction industry: a systematic review and interrelationships. Issue 6 (26th April 2023) - Yevu, Sitsofe Kwame; Yu, Ann Tit Wan; Darko, Amos
Abstract: Many studies have explored numerous barriers to e-procurement adoption in the construction industry. However, a comprehensive review of literature to reveal the interconnectivity among the barriers is still lacking. This study aims to conduct a systematic review and to reveal the relationships among e-procurement barriers in literature. Through a systematic review technique, 61 relevant papers were extracted. Thirty-four barriers were identified and categorized into organizational, technological legal and cultural barriers. Further, network analysis was employed to depict the complex interrelationships among the barriers. Although the barriers related to change resistance and lack of trust were prominent and highly connected, there exist other significant connections among the barriers to e-procurement adoption. The study contributes to e-procurement body of knowledge by exploring the complex interrelationships among e-procurement barriers. Further, this study offers practitioners a guiding frame in the development of effective strategies that mitigate e-procurement barriers and relationships in the construction industry.